On a degenerate boundary value problem to the two-dimensional self-similar nonlinear wave system - Jiajia Liu; Yanbo Hu; Tiehong Zhao (Boundary Value Problems, 2019)
Abstract This paper focuses on a degenerate boundary value problem arising from the study of the two-dimensional Riemann problem to the nonlinear wave system. In order to deal with the parabolic degeneracy, we introduce a partial hodograph transformation to transform the nonlinear wave system into a new system, which displays a clear regularity–singularity structure. The local existence of classical solutions for the new system is established in a weighted metric space. Returning the solution to the original variables, we obtain the existence of classical solutions to the degenerate boundary value problem for the nonlinear wave system.